Systematic review of correlates and determinants of physical activity in persons with multiple sclerosis - Streber, René; Peters, Stefan; Pfeifer, Klaus (Archives of physical medicine and rehabilitation, 2016)
OBJECTIVE: To review the current evidence regarding correlates and determinants of physical activity (PA) in persons with multiple sclerosis (pwMS). DATA SOURCES: Pubmed and Scopus (1980 to January 2015) and reference lists of eligible studies. STUDY SELECTION: Eligible studies (i) include adults with MS, (ii) have a cross-sectional or prospective observational design or (iii) examine the effect of a theory-based intervention trial on PA including a mediation analysis, (iv) apply a quantitative assessment of PA and correlates or proposed mediators and (v) are published in English or German. DATA EXTRACTION: Two reviewers independently evaluated the risk of bias, extracted data and categorized variables according to the International Classification of Functioning, Disability and Health (ICF). DATA SYNTHESIS: Consistency and the direction of associations were evaluated with a semi-quantitative approach. Fifty-six publications with data from observational studies and two interventional studies provided evidence for 86 different variables. Consistent correlates of PA were the disability level, walking limitations in particular, PA-related self-efficacy and self-regulation constructs as well as employment status and educational level. One interventional study provided evidence for a causal relationship between self-regulation and PA. However, 59 of 86 of all investigated variables in observational studies are based on one or two study findings, and the majority of results stem from cross-sectional designs. CONCLUSIONS: Beside the importance of the general disability level and walking limitations, the results highlight the importance of personal factors, such as PA-related self-efficacy, self-regulatory constructs and sociodemographic factors. Limitations and implications of the current review are discussed. Research that is more rigorous is needed to better understand what affects PA in pwMS.
Keywords: Health Behavior; Health Promotion; Motor Activity; Multiple Sclerosis